Species and genetic diversity of nontuberculous mycobacteria in suspected tuberculosis cases in East Azerbaijan, Iran: a cross-sectional analysis - Roshdi Maleki, Mehdi (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionThe incidence of nontuberculous mycobacterial (NTM) infections has increased worldwide, attracting attention in routine diagnostic settings, particularly among patients with suspected tuberculosis. This study aimed to acquire knowledge of NTM infections in patients with suspected tuberculosis and to evaluate the genetic diversity of the strains.MethodsIn this study, 230 clinical specimens were collected from suspected tuberculosis patients. Following decontamination with N-Acetyl-L-cysteine–sodium hydroxide (NALC-NaOH), the sediments of specimens were inoculated onto Löwenstein–Jensen medium and then incubated at 37°C for 8 weeks. The samples that yielded positive cultures were evaluated through the sequencing of conserved fragments of IS6110 and hsp65. For those samples that were not identified as part of the M. tuberculosis complex (MTC) by IS6110 PCR, further analysis was conducted via PCR to detect fragments of the hsp65 gene.ResultsTwenty-one NTM species were isolated from 230 clinical specimens (14 NTM from pulmonary specimens and 7 from extrapulmonary specimens). Among these, 12 (57.14%) were rapid-growing mycobacteria (RGM), and 9 (42.85%) were slow-growing mycobacteria (SGM). No M. avium complex (MAC) was identified in any of the specimens. Notably, the M. kansasii, M. gordonae, and M. abscessus strains presented significant genetic diversity.ConclusionsThe prevalence of infections attributed to nontuberculous species surpasses that attributed to tuberculosis. These findings underscore the importance of exploring NTM species in individuals suspected of having TB.